Adolescent and pediatric sports injuries - Ryu, R. K. N.; Fan, R. S. P. (Pediatric Clinics of North America, 1996)
Rather than a scholarly treatise debating the advantages of arthroscopic versus open stabilization in adolescents with shoulder instability, this article provides a concise and useful reference for practicing pediatricians whose care includes young athletes. With the ever-increasing number of boys and girls participating in organized sports, specific injury patterns, often dependent on sport and gender, have been identified. This article identifies the most common sports injuries, focusing on mechanism of injury, pathoanatomy, the history and physical findings, as well as recommendations for initial diagnostic studies and treatment. For injuries requiring a timely referral, a clear imperative is noted. Special consideration is given to skeletally immature patients whereas those who are skeletally mature may be treated as adults.